2007
DOI: 10.1007/s00268-006-0054-0
|View full text |Cite
|
Sign up to set email alerts
|

Extended Resection for Thyroid Disease has Less Operative Morbidity than Limited Resection

Abstract: Background: Theodor Kocher, surgeon and Nobel laureate, has influenced thyroid surgery all over the world: his treatment for multinodular goiter-subtotal thyroidectomy-has been the ''Gold Standard'' for more than a century. However, based on a new understanding of molecular growth mechanisms in goitrogenesis, we set out to evaluate if a more extended resection yields better results. Methods: Four thousand three hundred and ninety-four thyroid gland operations with 5,785 ''nerves at risk'' were prospectively an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 23 publications
2
6
0
1
Order By: Relevance
“…The present results emphasize our previously reported findings [10], now over a period of 39 years, namely that an extended thyroid resection is associated with a significantly reduced rate of permanent nerve palsy and hypoparathyroidism compared to subtotal resection. The risk of morbidity was significantly lower in the second study period due to (a) change in general surgical strategy, meaning hemithyroidectomy in all eligible patients with unilateral benign thyroid diseases or total thyroidectomy in bilateral benign disease, and (b) change in surgical technique with obligatory visualization of the recurrent laryngeal nerves and the parathyroid glands.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The present results emphasize our previously reported findings [10], now over a period of 39 years, namely that an extended thyroid resection is associated with a significantly reduced rate of permanent nerve palsy and hypoparathyroidism compared to subtotal resection. The risk of morbidity was significantly lower in the second study period due to (a) change in general surgical strategy, meaning hemithyroidectomy in all eligible patients with unilateral benign thyroid diseases or total thyroidectomy in bilateral benign disease, and (b) change in surgical technique with obligatory visualization of the recurrent laryngeal nerves and the parathyroid glands.…”
Section: Discussionsupporting
confidence: 79%
“…In spite of sufficient dietary iodine intake in the present day, multinodular goiter remains an endemic disease in Switzerland [3]. Further research and understanding of the molecular growth mechanism in goitrogenesis [4][5][6] and an inacceptable high recurrence rate associated with subtotal thyroidectomy led endocrine surgeons to adopt a more extended surgical resection for benign multinodular goiter disease [7][8][9][10][11]. Previous studies showed that total thyroid resection is a safe procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Aufgrund der hierdurch erreichten Reduktion des relativen und absoluten Risikos würde jeder 38. Patient von einer radikaleren Resektion profitieren [47]. Auch Dralle kal- [44,52].…”
Section: Tab 1 Zusammenfassung Vergleichender Studien Zur Operativenunclassified
“…Previous studies on TR at our institution could not rectify limited resections based on nerve injury rates. 44 However, guidelines recommending TR as the treatment of choice also take into consideration that secondary total thyroidectomy for disease recurrence has a higher risk of complications than primary total thyroidectomy. Very recently, Bilimoria et al advocated TR in all PTC patients with tumors greater than 1 cm based on a very large population from the National Cancer Data Base.…”
Section: Extent Of Resectionmentioning
confidence: 99%